Diagnosis and management of bile acid diarrhoea: a survey of UK expert opinion and practice - Walters, Julian R F (Frontline Gastroenterol, 2019)
OBJECTIVE: Bile acid diarrhoea (BAD), which includes bile acid malabsorption, causes a variety of digestive symptoms. Diagnostic rates and management vary considerably. We conducted a survey of current practice to review expert opinion and provide guidance on diagnosis and management. DESIGN/METHOD: An online survey was conducted of clinical members of the UK Bile Acid Related Diarrhoea Network, who had all published research on BAD (n=21). Most were National Health Service consultants who had diagnosed over 50 patients with the condition. RESULTS: The preferred terminology was to use BAD, with primary and secondary to classify causes. A wide range of presenting symptoms and associated conditions were recognised. SeHCAT (tauroselcholic acid) was the preferred diagnostic test, and 50% of respondents thought general practitioners should have access to this. Patients who met the Rome IV diagnostic criteria for functional diarrhoea, irritable bowel syndrome (IBS) with predominant diarrhoea or postcholecystectomy diarrhoea were usually investigated by SeHCAT, which was used sometimes in other types of IBS. Treatment with a bile acid sequestrant was offered to patients with low SeHCAT values, with expected response rates >70% in the most severe. Colestyramine was the usual sequestrant, starting between 2 g and 8 g daily; colesevelam was an alternative. In patients who had an incomplete response, increasing the dose, changing to an alternative sequestrant, use of loperamide and a low fat diet were suggested. Recommendations for follow-up and to improve the overall patient experience were made. CONCLUSION: This expert survey indicates current best practice in the diagnosis and management of BAD.